2012
DOI: 10.1021/ja303498q
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Basis for Asymmetric Seeding Barrier in Filaments of Three- and Four-Repeat Tau

Abstract: Tau pathology in Alzheimer’s disease is intimately linked to the deposition of proteinacious filaments, which akin to infectious prions, have been proposed to spread via seeded conversion. Here we use double electron–electron resonance (DEER) spectroscopy in combination with extensive computational analysis to show that filaments of three- (3R) and four-repeat (4R) tau are conformationally distinct. Distance measurements between spin labels in the third repeat, reveal tau amyloid filaments as ensembles of know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
78
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 62 publications
10
78
0
Order By: Relevance
“…The locations of the HXPGGG motifs in the K18 monomer[58] (A) and K18 fibril[36, 59] (B). C. A model of full-length tau fibril structure[60].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The locations of the HXPGGG motifs in the K18 monomer[58] (A) and K18 fibril[36, 59] (B). C. A model of full-length tau fibril structure[60].…”
Section: Figurementioning
confidence: 99%
“…DC8E8 is able to discriminate between the healthy and diseased tau proteome, making its epitopes suitable targets, and DC8E8 a suitable candidate molecule, for AD immunotherapy. [57] Figure 3 shows the location of the four motifs in K18 monomer[58] and K18 fibril[36, 59]. With the addition of the C- and N-terminal residues, the PGGG motifs could be buried inside.…”
Section: Introductionmentioning
confidence: 99%
“…Both 3R- and 4R-tau are included in the NFTs of AD [36]. However, similar to Aβ, there may be isoform-specific characteristics in the aggregation and fibril-forming capacity of tau [37]. In general, with AD and other tauopathies, the dysregulation of tau phosphorylation and its subsequent aggregation into NFT structures impairs neuronal functioning and ultimately leads to cell death.…”
Section: Alzheimer’s Disease Pathologymentioning
confidence: 99%
“…Both amyloid seeds from hIAPP and Aβ peptides could serve as the interacting precursors to mutually promote the amyloid elongation. Consistently, a number of studies have reported that amyloids from different species or with different sequences can overcome cross-seeding barriers to form cross-seeding aggregates and fibrils via the elongation pathway if they have close structural similarity, including tau-k18 and tau-k19 [84][85][86][87] , Aβ and tau 29 , and hIAPP and rIAPP 25 . Meanwhile, it is interesting to note that the tail-tail model also had a relatively higher population of 21.1%.…”
Section: Structural Populations Of Polymorphic Aβ-hiapp Assembliesmentioning
confidence: 80%